Identification of stretch-shortening cycles in different sports - Komi, P. V.; Ishikawa, M.; Linnamo, V. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
In sports the stretch-shortening cycle (SSC) muscle actions are obviously natural. They are partly responsible for making the muscular performance more economical and/or better as compared to the use of isolated forms of muscle actions. In sport activities SSC can be traditionally identified by certain kinematic and electromyographic methods. An attempt is made to describe how one can go beyond these more simple ways by applying portable ultrasonography (US) to record fascicle-tendon interactions during various movements ranging in intensity from low to maximum. The observed results from a number of studies indicate that the original definition of SSC cannot be used to describe the SSC at the MTU levels of all muscles and all exercise conditions. However, the greatest merit of this US application is in its strength to explain more of the mechanism how the fascicle-tendon interaction differs between muscles and how the elastic energy may be involved in the performance potentiation.